Telaah Proses Kurikulum - Endang Kaswati; Desty Isnaini; Muhammad Abdurrohman; Mustafiyanti Mustafiyanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Curriculum review is a crucial process for ensuring that educational programs remain relevant, effective, and aligned with current needs and societal expectations. This journal focuses on the examination of curriculum review processes, exploring various approaches, methodologies, and frameworks employed to evaluate and refine curriculum content, pedagogy, and assessment strategies. The journal delves into the critical aspects of curriculum review, encompassing stakeholder involvement, data collection and analysis, identification of strengths and weaknesses, and the formulation of recommendations for improvement. It also highlights the significance of contextual factors, such as cultural, social, and economic considerations, in shaping curriculum review processes.